2013
DOI: 10.5185/amlett.2012.11466
|View full text |Cite
|
Sign up to set email alerts
|

Post-deposition Annealing Controlled Structural And Optical Properties Of RF Magnetron Sputtered MoO3 Films

Abstract: MoO3 films were deposited on Corning glass and silicon substrates held at room temperature (303 K) by RF magnetron sputtering of metallic molybdenum target at a fixed oxygen partial pressure of 4x10 -4 mbar and sputter pressure of 4x10 -2 mbar. The as deposited films were annealed in air at different temperatures in the range 473 -673 K. X-ray diffraction studies suggest that the as-deposited and the films annealed at 473 K were amorphous in nature, while those annealed at 573 and 673 K were polycrystalline wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The present optical band gap data are well matched with those reported in literature for different oxidation state of vanadium oxide505152 as well as molybdenum oxide5053. Further, the data presented in Table 2 confirmed that the optical band gap decreased with the increase in VO-MO film thickness.…”
Section: Resultssupporting
confidence: 90%
“…The present optical band gap data are well matched with those reported in literature for different oxidation state of vanadium oxide505152 as well as molybdenum oxide5053. Further, the data presented in Table 2 confirmed that the optical band gap decreased with the increase in VO-MO film thickness.…”
Section: Resultssupporting
confidence: 90%
“…It can be observed from Figure that the transmission values are relatively low in the visible region for all the α‐MoO 3 thin films, which may be attributed to the heat treatment at low temperature (350 °C). In this respect, Subbarayudu et al . have reported that the low transmission in the MoO 3 thin films thermally treated at low temperatures is due to the presence of oxygen vacancies, whereas these vacancies can scatter the light photons.…”
Section: Resultsmentioning
confidence: 99%
“…For sputtered MoO 3 thin films, post annealing at temperatures of 300-400 °C gives rise to the formation of orthorhombic α-phase and monoclinic β-phase crystalline structure [12] depending on the annealing temperature. The crystalline size and quality increases with annealing temperature, which at some point also changes optical properties.…”
Section: Thermal Stabilitymentioning
confidence: 99%